1933
DOI: 10.1172/jci100529
|View full text |Cite
|
Sign up to set email alerts
|

The Rôle of Thyroxin Iodine and Total Organic Iodine in the Calorigenic Action of Whole Thyroid Gland

Abstract: In a previous communication (1) we have shown that thyroxin polypeptide has a calorigenic action identical to that of pure racemic thyroxin when the two are given, intravenously, in doses containing equal quantities of iodine. It was further shown that thyroxin polypeptide is as active when taken by mouth as when given intravenously. These facts can be taken advantage of for the further study of thyroid physiology. The present paper deals with the calorigenic activity of certain brands of whole thyroid gland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1934
1934
1964
1964

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The role of physical properties such as solubility or optical activity must be identified. The possibility of enhancement of physiologic potency brought about by alteration in physical state has been mentioned in previous communications (1) (2). In the first paper of this series (1) it was shown that racemic crystalline thyroxin and optically active thyroxin polypeptide had equal calorigenic activity when given in equal iodine dosage.…”
mentioning
confidence: 93%
“…The role of physical properties such as solubility or optical activity must be identified. The possibility of enhancement of physiologic potency brought about by alteration in physical state has been mentioned in previous communications (1) (2). In the first paper of this series (1) it was shown that racemic crystalline thyroxin and optically active thyroxin polypeptide had equal calorigenic activity when given in equal iodine dosage.…”
mentioning
confidence: 93%
“…This hypothesis involves 3 assumptions: that all the dried thyroid is absorbed from the alimentary tract; that it is quantitatively as effective as the natural hormone; and lastly, that the hypothyroid patient's own gland contributes no hormone. Although complete intestinal absorption has not been proved directly, it is strongly suggested by the fact that in the treatment of human hypothyroidism, desiccated thyroid is even more effective than intravenous thyroxine in iodoequivalent amounts (19). The validity of the second assumption has already been discussed.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for the apparent difference in the effect of very large doses of diiodotyrosine in tadpoles and man is not clear. Means, Lerman and Salter (27) have recently advanced the hypothesis that diiodotyrosine assumes calorigenic properties when linked with amino-acids in iodothyreoglobulin.…”
Section: Commentmentioning
confidence: 99%